The position of soft power in Turkish foreign policy towards the Middle East region after 2002 (قضايا سياسية, 2023)
This study explores the dynamics of Turkish soft power in the contemporary era, focusing on the post-Justice and Development Party period. Turkey's increasing influence on the regional stage, driven by a strategic expansion of its soft power, forms a crucial aspect of its foreign policy. This research aims to comprehensively analyze the concept of soft power within the Turkish context, shedding light on its dimensions and role in achieving political objectives regionally.The study is structured into three axes: the first delves into the theoretical foundations of soft power, its dimensions, and its integration into Turkish foreign policy. The second axis examines the diverse resources and components constituting Turkish soft power. The third axis specifically focuses on Turkey's strategies for deploying soft power in the Middle East. The study employs a systematic approach, combining descriptive and analytical methods. The descriptive approach elucidates shifts in Turkish foreign policy since the ascent of the Justice and Development Party. Simultaneously, the analytical approach seeks to dissect the consequences of employing soft power, offering insights into its potential future impact.Concentrating on cultural collaboration and Turkey's initiatives to disseminate its language, literature, and arts in the region, the study aims to unravel Turkey's role and influence. Additionally, it investigates the impact of Turkish arts, media, and scholarships on enhancing understanding of Turkish culture among students and researchers in the region. This research not only contributes to the understanding of Turkish soft power but also holds implications for broader international relations.